Prevalence, spatial distribution, and determinants of wasting among children under five in Senegal: spatial and multilevel analyses of the 2023 Senegal Demographic and Health Survey - Tamir, Tadesse Tarik; Tekeba, Berhan; Aemro, Agazhe; Wassie, Mulugeta; Mekonen, Enyew Getaneh (Frontiers in Public Health, 2025)
IntroductionChild undernutrition remains a persistent public health challenge across sub-Saharan Africa. Wasting, which is characterized by severe muscle wasting and heightened vulnerability to morbidity and mortality, poses a particularly grave concern in the region. Recently, Senegal’s children faced a number of socioeconomic challenges, including the lingering effects of the COVID-19 pandemic, disruptions caused by the war between Russia and Ukraine, persistent security threats from the Sahel crisis, and internal socio-political tensions. Hence, this study aimed to assess the prevalence, spatial distribution, and determinants of wasting among children under five in Senegal.MethodA secondary analysis of the 2023 Senegal Demographic and Survey dataset was conducted. A total weighted sample of 4,392 children under the age of 5 years was included in the analysis. ArcGIS 10.7 and Stata 17 were utilized for spatial analysis and multilevel regression, respectively. The fixed effect was evaluated by calculating the adjusted odds ratio with a 95% confidence interval. We considered the association between explanatory variables and outcomes to be significant when the p-value was less than the predetermined level of significance (0.05).ResultThe prevalence of wasting among children under the age of five in Senegal was 10.29% at a 95% CI of 9.42 to 11.24%. Childhood wasting exhibited a clustered pattern across regions of Senegal. The hot spot clusters of elevated wasting prevalence were found to be concentrated in the Diourbel, Tambacounda, and Matam regions of Senegal. Small birth size, poor household wealth index, rural residence, and region were significant determinants of wasting among children under 5 years old.ConclusionChildhood wasting remains a significant public health concern in Senegal, with a prevalence much higher than the global 2025 target. Spatial clustering of high wasting prevalence in the Diourbel, Tambacounda, and Matam regions highlights the need for targeted interventions in these high-risk areas. The identified risk factors, including small birth size, poor household wealth, rural residence, and regional disparities, should guide the design and implementation of effective nutritional programs and policies. Addressing the underlying determinants of childhood wasting is crucial to improve child health and development outcomes in Senegal.